Pengembangan Modul Perubahan Lingkungan Dengan Pembuatan Kompos Sebagai Sumber Belajar - Martala Sari*; Ermina Sari; Raudhah Awal; Natalia Denifitria (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
Learning Biology on environmental change material that needs updating is in line with curriculum demands by making compost as a learning resource that can solve the problem of organic waste that is around us. The purpose of this study was to develop a module for environmental change by making compost as a learning resource for class X high school students. The research subjects at SMA Santa Veronika Pekanbaru obtained information that the teaching materials used were printed books, modules without pictures. This research was conducted using the Research And Development or (R & D) method using ADDIE. In this study, it was limited to stage 3. The instrument used was in the form of assessment criteria to determine the feasibility of the environmental change module by making compost, knowing material experts, learning experts and student responses using a Likert scale by administering an assessment questionnaire. Based on the results of the material expert validation, an average yield of 89.48% was obtained. Learning Media Experts obtained an average yield of 82.00%, thus the developed module was declared valid for use. After conducting the validity of the module to the expert, then the module is tested on student responses. It was obtained that the students' responses with a percentage of 86.36% were stated in the good and proper predicate, thus the modules that were developed were good and suitable for use in the learning process.